학동기 및 청소년 천식 소아들의 임상 양상과 천명 시작 시기와의 관련성 - 장광천; 심정연; 안영민; 정진아; 김성원; 정혜리; 대한 소아알레르기 호흡기학회; 학동기 청소년 천식 연구회 (Allergy asthma & respiratory disease, 2015)
Purpose: We aimed to investigate the clinical characteristics and their relationship with the onset age of wheeze in school-age children and adolescents with asthma. Methods: Three hundred twenty-six patients, aged 6 to 19 years, diagnosed with asthma at 6 hospitals from Seoul, Gyeonggi, Daegu, and Busan were enrolled. They were categorized into 3 groups by the onset age of wheeze: group A, early onset (age <3 years); group B, preschool onset (age 3–6 years); group C, late onset (age ≥6 years). Clinical characteristics including atopic sensitization, family history, combined allergic diseases, severity of asthma, and influence of asthma on daily life were examined. A history of hospitalization for early lower respiratory infection (LRI) and environmental tobacco smoking were studied and lung function tests were also performed. Results: There was no difference in demographics, prevalence of atopy, combined allergic diseases, and family history of allergy between 3 groups. A history of sever LRI in early life was more common in groups A and B compared with group C. Sensitization to Dermatophagoides pteronyssinus was more prevalent in groups A and B than in group C. Forced expiratory flow between 25% to 75% (FEF25%-75%) was lower in groups A and B than in group C, and methacholine PC20 (provocative concentration of methacholine causing a 20% fall in forced expiratory volume in one second) was lowest in group B. Significantly lower FEF25%-75% and methacholine PC20 were observed in the patients who had been hospitalized with LRI in early life. Conclusion: Our study shows significant difference in lung function and atopic sensitization in relation to the onset age of wheeze in school-age children and adolescents with asthma, and suggests that early LRI might contribute to the development of asthma in early life. KCI Citation Count: 0